Phosphorylation of Intrinsically Disordered Regions in Remorin Proteins - Marín, Macarena; Ott, Thomas (Frontiers in Plant Science, 2012)
Plant-specific remorin proteins reside in subdomains of plasma membranes, originally termed membrane rafts. They probably facilitate cellular signal transduction by direct interaction with signalling proteins such as receptor-like kinases (RLKs) and may dynamically modulate their lateral segregation within plasma membranes. Recent evidence suggests such functions of remorins during plant-microbe interactions and innate immune responses, where differential phosphorylation of some of these proteins has been described to be dependent on the perception of the microbe-associated molecular pattern (MAMP) flg22 and the presence of the NBS-LRR resistance protein RPM1. A number of specifically phosphorylated residues in their highly variable and intrinsically disordered N-terminal regions have been identified. Sequence diversity of these evolutionary distinct domains suggests that remorins may serve a wide range of biological functions. Here, we describe patterns and features of intrinsic disorder in remorin protein and discuss possible functional implications of phosphorylation within these rapidly evolving domains.